Association of Valproic Acid Use With Post-Myocardial Infarction Heart Failure Development: A Meta-Analysis of Two Retrospective Case-Control Studies - Joseph D. English PharmD; Shuo Tian PhD; Zhong Wang PhD; Jasmine A. Luzum PharmD, PhD (SAGE Publishing, 2022)
Background: Despite advances in treatments, myocardial infarction (MI) remains a significant cause of morbidity and mortality worldwide. Our team has previously shown that valproic acid (VPA) is cardio-protective when administered to rats post-MI. The aim of this study was to investigate the association of VPA use with post-MI heart failure (HF) development in humans. Methods: This study was a random effects meta-analysis of two retrospective case-control studies collected from electronic health record (Michigan Medicine) and claims data (OptumInsight). Cases with an active prescription for VPA at the time of their MI were matched 1:4 to controls not taking VPA at the time of their MI by multiple demographic and clinical characteristics. The primary outcome, time-to-HF development, was analyzed using the Fine-Gray competing risks model of any VPA prescription versus no VPA prescription. An exploratory analysis was conducted to evaluate the association of different VPA doses (≥1000 mg/day vs <1000 mg/day vs 0 mg/day VPA). Results: In total, the datasets included 1313 patients (249 cases and 1064 controls). In the meta-analysis, any dose of VPA during an MI tended to be protective against incident HF post-MI (HR = 0.87; 95% CI = 0.72-1.01). However, when stratified by dose, high-dose VPA (≥1000 mg/day) significantly associated with 30% reduction in risk for HF post-MI (HR = 0.70; 95% CI = 0.49-0.91), whereas low-dose VPA (<1000 mg/day) did not (HR = 0.95; 95% CI = 0.78-1.13). Conclusion: VPA doses ≥1000 mg/day may provide post-MI cardio-protection resulting in a reduced incidence of HF.